(untitled) (Global Journal of Human-Social Science, 2012)
1 Purpose This study investigated gender religious affiliation institution of learning and academic level as factors predicting sexual risk susceptibility among university undergraduates drawn from two Univer - sities in South-Western Nigeria 2 Methods Using an ex-post facto survey research design and random sampling methods a total of 320 participants were selected for the study 118 36 9 were male 202 63 1 were female Validated scale was used for data collection Four hypotheses were stated two of which were analyzed using t-test of independent means while the remaining two were analyzed using a univariate analysis of variance